2015
DOI: 10.1002/ece3.1784
|View full text |Cite
|
Sign up to set email alerts
|

Out of Africa: evidence of the obligate mutualism between long corolla tubed plant and long‐tongued fly in the Himalayas

Abstract: Summary Mutualism between long corolla tubed plants and their potential pollinators, long‐tongued flies, is a classic example of coevolution, but to date, has only been reported from the regions of southern Africa. Many plant species from the Himalayas also show botanical characteristics that could be consistent with pollination by long‐tongued flies. Here, we seek the evidence of the “long‐tongued‐long tubed fly/flower” mutualism out of Africa, in a different continent and climatic region, the Himalayas.Flora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 59 publications
6
56
0
Order By: Relevance
“…Roscoea species are largely endemic to the Himalayas and the Hengduan Mountains, and exhibit extremely diverse floral traits that may link to local adaptations and/or distinct pollination syndromes (Zhang & Li, 2008;Zhang et al, 2011;Fan & Li, 2012;Paudel et al, 2015Paudel et al, , 2016. Compared to previous phylogenetic results (Ngamriabsakul et al, 2000), this study produced a more informative phylogenetic backbone using nrDNA and cpDNA from which testable hypotheses can be drawn for future in-depth speciation studies for this group.…”
Section: Discussionmentioning
confidence: 96%
“…Roscoea species are largely endemic to the Himalayas and the Hengduan Mountains, and exhibit extremely diverse floral traits that may link to local adaptations and/or distinct pollination syndromes (Zhang & Li, 2008;Zhang et al, 2011;Fan & Li, 2012;Paudel et al, 2015Paudel et al, , 2016. Compared to previous phylogenetic results (Ngamriabsakul et al, 2000), this study produced a more informative phylogenetic backbone using nrDNA and cpDNA from which testable hypotheses can be drawn for future in-depth speciation studies for this group.…”
Section: Discussionmentioning
confidence: 96%
“…and Philoliche longirostris Hardwicke. At all sites, R. purpurea was the most abundant species in flower during our observation period and P. longirostris was observed to be its exclusive floral visitor (Paudel et al ., ). Each site covers c .…”
Section: Methodsmentioning
confidence: 97%
“…Our preliminary field observations indicated that inflorescence height, floral display area, and corolla tube length of R. purpurea , as well as proboscis length of P. longirostris , varied across the wide range of habitats in which the populations occur. Moreover, the variation in floral length and fly proboscis length appeared to be concomitant, in a manner consistent with coevolution (Paudel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As previous studies have suggested, an increase in the number of flowers is always selected because of the upper limit to seed production and attractiveness to pollinators (Grindeland, Sletvold, & Ims, ; Mitchell, Karron, Holmquist, & Bell, ; Sandring & Ågren, ). Selection on corolla tube or spur length can be attributed to interactions with local pollinators (Huang, Wang, & Sun, ), for example, coevolutionary elaboration between corolla tube length of Roscoea purpurea and its local pollinators (Paudel et al., , ). However, our results support these hypotheses at only one of our studied populations.…”
Section: Discussionmentioning
confidence: 99%